Tahliil Istikhdaami al-Mufradaat al-'Arabiyyat al-Muqtaridhah Fii al-Lughat al-Induuniisiyyat - Hermiwati, Hermiwati; Hadziq, Muhammad Fadhil; Pelealu, Nanda Dzikrillah; Mustofa, Syaiful (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2024)
The objectives of this study were to determine the meaning of the word "assimilation" and how it is commonly used in daily life. The research method utilized in this study was qualitative, employing a descriptive approach. Data collection involved conducting interviews and gathering documentation, while data analysis was performed using the Mills and Huberman method for data reduction, presentation, and extraction. The findings of this study indicate that the borrowed forms in the Indonesian language from Arabic are primarily related to three categories: nouns, adjectives, and verbs. Examples of borrowed nouns include chair, mosque, court, Islam, and Ramadan. Examples of borrowed adjectives include peace, justice, knowledge, poverty, ignorance, and injustice. Examples of borrowed verbs include jihad, marriage, zakat, friendship, and worship. الملخص كانت أهداف هذه الدراسة هو معرفة ما هي كلمة استيعاب وكيف يتم استخدام شكل كلمة استيعاب في كثير من الأحيان في الحياة اليومية. الطريقة المستخدمة في هذه الدراسة هي طريقة البحث النوعي ذات المنهج الوصفي. وطريقة جكع البيانات باستخدام المقابلة والتوثيق وطريقة تحليل البيانات من خلال طريقة ميلس وهبرمان من تخفيض البيانات وعرضها واستخلاصها. ونتائج هذه الدراسةتدل على أن أشكال المقترضة في اللغة الإندونيسية من اللغة العربية يعنى بثلاثة محاور هي أشكال الأسماء، أشكال الصفات، وأشكال الأفعال في اللغة الإندونيسية. أما بالنسبة إلى الأسماء مثل كرسي، ومسجد، ومحكمة، وإسلام، ورمضان. أما بالنسبة إلى الصفات كمثل سلام وعادل، وعالم، ومسكين، وجاهل، وظالم. أما بالنسبة إلى الأفعال كمثل وجهاد، ونكاح، وزكاة، وصداقة، وعبادة.